Non-financial constraints to scaling-up small and medium-sized energy enterprises: Findings from field research in Ghana, Senegal, Tanzania and Zambia. (January 2015) - Haselip, James; Desgain, Denis; Mackenzie, Gordon
Abstract: In the context of the 'decade for sustainable energy' (2014–2024) under the UN's Sustainable Energy for All initiative, this article presents findings from primary research conducted into the 'African Rural Energy Enterprise Development' (AREED) programme. AREED was a donor-backed effort to support small and medium-sized energy enterprises, implemented in five countries by United Nations Environmental Programme between 2002 and 2012, as a means to expand access to sustainable energy products and services in sub-Saharan Africa. While access to affordable finance was found to be the primary constraint to establishing and expanding local small and medium-sized energy businesses, a range of significant non-financial constraints were also identified. This article provides a critical evaluation of these non-financial constraints as they were encountered in Ghana, Senegal, Tanzania and Zambia, based on the findings of a wider study into the key outcomes of the AREED project. These barriers include the institutional frameworks, human capacities and social and cultural factors.